VARIABILITY AND microRNA EXPRESSION LEVEL IN TISSUES OF HEAD AND NECK TUMORS - Е. G. Nikitina; L. N. Urazova; О. V. Cheremisina; D. Е. Kulbakin; S. N. Stegniy (Сибирский онкологический журнал)
Small non-coding RNAs (miRNAs) are not only an important regulator of gene expression by participating in almost all basic processes in the cell, but are specific molecules and can be used for many applications in clinical diagnostics. In our study, we assessed the level of miRNA expression in tumor tissue of patients with head and neck tumors of various sites. New data regarding the expression pattern of eight miRNAs in tumor tissue from patients with cancer of the larynx, tongue and papillary thyroid carcinoma, namely: miR-18a, -21, -155, -200a, -200c, -205, -221 and -494 were obtained. The spectrum of miRNA-specific localizations was analyzed, suggesting the existence of differences in the mechanisms of participation of the same miRNA in carcinogenesis of tumors of different epitopes of the head and neck. The panel of miR-200a, -200c, -21 and -205 was shown to be specific for determining the two locations (laryngeal and thyroid cancers) and probably can be used to define the site of a secondary tumor and / or metastasis of unknown origin.